2018
DOI: 10.3390/su10103740
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0 and Sustainability Implications: A Scenario-Based Analysis of the Impacts and Challenges

Abstract: The new evolution of the production and industrial process called Industry 4.0, and its related technologies such as the Internet of Things, big data analytics, and cyber–physical systems, among others, still have an unknown potential impact on sustainability and the environment. In this paper, we conduct a literature-based analysis to discuss the sustainability impact and challenges of Industry 4.0 from four different scenarios: deployment, operation and technologies, integration and compliance with the susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
318
0
26

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(349 citation statements)
references
References 66 publications
5
318
0
26
Order By: Relevance
“…From the sustainability supply chain viewpoint, sustainable benefits can be obtained from the use of IT or Industry 4.0 related technologies as information systems integration improvement to enhance the supply chain information transparency and processing capability. Such benefits include: transparency of process, machinery, stock, or logistics data to facilitate traceability of commodity flow to increase resource and energy efficiency; reduction of waste, logistics process and delivery errors and damaged goods; shorter set-up and lead times as well as faster machine speed to facilitate faster and more flexible, efficient, and higher quality response to customer demands; reduction of time-to-market in new product design, thus supporting a firm to effectively and efficiently manage operational contingencies and enhance performance [29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Supply-chain Management Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the sustainability supply chain viewpoint, sustainable benefits can be obtained from the use of IT or Industry 4.0 related technologies as information systems integration improvement to enhance the supply chain information transparency and processing capability. Such benefits include: transparency of process, machinery, stock, or logistics data to facilitate traceability of commodity flow to increase resource and energy efficiency; reduction of waste, logistics process and delivery errors and damaged goods; shorter set-up and lead times as well as faster machine speed to facilitate faster and more flexible, efficient, and higher quality response to customer demands; reduction of time-to-market in new product design, thus supporting a firm to effectively and efficiently manage operational contingencies and enhance performance [29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Supply-chain Management Systemsmentioning
confidence: 99%
“…Thus, managers should recognize the role of supply-chain capabilities, in terms of information exchange, activity coordination, activity integration as well as responsiveness, for fully realizing the value of IT application. As Barney [107] and Bonilla et al [30] discuss, IT application can ensure sustainable benefits only when they are properly integrated with sustainable development goals and inserted in eco-operation supply chain platform processes. The results (Figure 2) show that the respondents in this study demonstrated high standardized parameter estimates in planning and forecast factors with regard to SCMS application; information exchange ability and responsive ability with regard to SCC; new product development with regard to operational performance; and growth rate with regard to financial performance.…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When pushing the paradigms of current science, both natural and social, there are a lot of discussions about the phenomenon of digitalization. This phenomenon has, in the last decade, caused profound changes in the natural environment, society, and, consequently, in the business economy (Scholz et al, 2018;Bonilla et al, 2018). Its importance for the progress of human species can be rivaled with such events as the development of agriculture or mastering the fire (Takács-Sánta, 2004;Scholz et al, 2018).…”
Section: Effects Of Digitalization On the Business Environmentmentioning
confidence: 99%
“…Current trends in economic and business practice are nowadays firmly focused on the changes that digitalization, which is showing itself in the form of the Industry 4.0 phenomenon, will bring (Müller et al, 2018;Bonilla et al, 2018;Piccarozzi et al, 2018). Digitalization has, especially in the last decade, had a severe impact on the economic system (Scholz et al, 2018) and, within it, the organizations (Mohelska & Sokolova, 2018).…”
Section: Introductionmentioning
confidence: 99%